Restless authors. - Taylor, Richard; Daley, David (Bookseller, 2004)
The article examines ways in which authors may try to escape from their contracts, and ways in which publishers may try to stop them. Most author/publisher contracts contain provisions for new editions and updates. Indeed, many contain clauses under which the publisher can compel the author to produce a new edition and, if the author cannot or will not do so, allow the publisher to commission a new edition from a new author. Publishers can contract with an author that the author will not compete, through another publisher, with his own work, but not that the author will not compete with other works on the publisher's list. If an author is tied into a multiple book deal, then this may give the publisher power to restrain them from leaving before their quota of books is delivered. However, an author may try to challenge the arrangement as an unlawful restraint of trade. The brave new world of electronic publishing has seen disagreements and gaps in some contracts that can cause confusion on the balance between the rights of publisher and author. INSET: Model clauses.